Teaching English Without An LMS: Creative Approaches to EFL Curriculum Implementation - Nurwanti, Nurwanti; Dollah, Syarifuddin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research examines the creative strategies used by English lecturers at Lakidende Unaaha University in delivering the EFL curriculum without the support of a Learning Management System (LMS). Using a qualitative case study approach, data was collected through interviews and classroom observations to explore how lecturers overcome challenges arising from limited technological infrastructure. Findings show that lecturers have successfully implemented student-centered strategies by incorporating local cultural content, encouraging collaboration, utilizing offline tools, and involving community resources. These approaches have improved learning outcomes, motivation, and cultural pride among students. Despite the absence of an LMS, this method fosters motivation, cultural pride, and social skills while providing alternative assessments and reflective practices for tracking student progress. However, these approaches require a lot of time and expertise, highlighting the need for institutional support in providing technological infrastructure and professional development. This research shows that even without an LMS, effective and meaningful education can be achieved, but continued progress requires greater support for educators and students to ensure long-term success.